Towards A Smart Village: Peningkatan Kesadaran Masyarakat Melalui Literasanctuary Berbasis Kearifan Lokal Untuk Membangun Kemandirian Ekonomi di Desa Segoropuro (Indonesian Version) - Nunuk Indarti; M. Mascun Andianto; Kiki Oktavia; Safitri Wulandari (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses community empowerment efforts in Segoropuro Village, Rejoso District, Pasuruan Regency, East Java Province, to overcome problems in education. Through a local wisdom-based Literasanctuary, this program integrates educational, economic and digitalization curricula. The theoretical framework includes increasing public awareness, the role of society in improving education, building economic independence, establishing literacy, empowering the creative economy, equality education programs. Implementation method for implementing the smart village program with 3 learning curricula, smart village mentoring program in Segoropuro literacy by the Pasuruan district education and culture office, monitoring program by the small and medium enterprise cooperative service. This article presents concrete steps towards a smart Segoropuro Village through literature based on local wisdom to build economic independence.